Dějiny Boha - Armstrong, Karen, 1944-; Moravcová, Martina; Kovařík, Štěpán; Kropáček, Luboš, 1939- (Praha : Argo, 1996)
monoteistické náboženstvá
judaizmus
kresťanstvo
islam
Armstrongová, Karen
Keywords: religionistika